Analisis Penerapan Prinsip Good Corporate Governance dalam Meningkatkan Kinerja Perusahaan pada Perusahaan Manufaktur Kayu PT DLI - Djati, Edgard Koesuma; Susilowati, Clara (Syntax Corporation, 2023)
This research aims to analyze the implementation of Good Corporate Governance (GCG) principles in enhancing the performance of PT DLI, a wooden manufacturing company in Indonesia. Using a qualitative approach, the study involved interviews with three key informants from various departments within the company. The research findings indicate that the application of GCG principles, particularly transparency, accountability, responsibility, independence, and fairness, has been carried out with some challenges. Despite these principles having a positive impact on the company's performance, there is still external intervention in decision-making that may hinder the company's independence. Therefore, this study provides an in-depth understanding of how the implementation of GCG can influence company performance and highlights the need for further steps to enhance the company's independence in decision-making.